Surgical management of thymic epithelial tumors in children: Lessons from the French Society of pediatric oncology and review of the literature. Issue 11 (17th August 2014) - Rod, J.; Orbach, D.; Verité, C.; Coze, C.; Stephan, J.L.; Varlet, F.; Thomas‐de‐Montpreville, V.; Reguerre, Y.; Besse, B.; Sarnacki, S.
Abstract Purpose We report the results of a French multicenter retrospective study based on a period of more than 30 years and a review of the literature in order to more clearly define the surgical approach and specific pediatric risk factors. Methods Clinical data of children comprising all histologic subtypes of thymic epithelial tumors (TET) treated between 1979 and 2009 in French pediatric oncology centers were retrospectively analyzed and discussed in the light of a review of all pediatric cases reported in the literature. Results Nine cases were identified, corresponding to five females and four males with a median age of 13 years (range: 7.5–17). Histologic subtypes were type AB (n = 1), type B (n = 5) and type C (n = 3). Treatment consisted of tumor resection (4 R0, 4 R1, 1 R2) via right anterior thoracotomy, posterolateral thoracotomy, left thoracoscopy, sternotomy and cervicosternotomy, and/or chemotherapy, mainly cyclophosphamide‐doxorubicin‐cisplatin (CAP; n = 5), and/or radiotherapy (n = 4). Two patients with TET type C died. All other patients are alive with a median follow‐up of 4 years (range: 1.5–20). Review of a total of 93 pediatric cases reported in the literature showed statistically significant associations between less favorable histologic subtypes and male gender (P = 0.012), advanced Masaoka stage (P < 0.001) and quality of resection (P < 0.001) respectively. Conclusions A review of the literature and our series identified several risk factors to take into account in the therapeutically decision. Complete resection through a sternotomy is highly recommended. Pediatr Blood Cancer 2014;61:1910–1915. © 2014 Wiley Periodicals, Inc.